The Relationship of Parenting Patterns with Students' Moral Behavior - Alnetia Dwi Kamirsa Amria; Netrawati Netrawati (Universitas Negeri Padang, 2021)
This type of research is descriptive correlational with a population of 489 students. Sampling of 240 students using the Slovin formula. The sampling technique used is Stratified Random Sampling. The data collection instrument was a parenting style questionnaire using a Likert scale and a student moral behavior questionnaire using a Likert scale. The data was processed using descriptive statistical analysis techniques and to test the relationship the data were analyzed using the Pearson Product Moment formula with the Statical Product and Service Solution (SPSS) version 20.0 program. The results of this study revealed that: (1) Parenting patterns are in the fairly good category, (2) the moral behavior of students is in the good category, (3) there is a positive and significant relationship between parenting patterns and students' moral behavior at MTsN 1 Padang. Pariaman with rtable of 0.138 and rcount of 0.564 with a significant level of 0.000. So the better the parenting style score, the better the students' moral behavior. Based on the findings of this study, it is expected that BK teachers or counselors can provide assistance in the form of Guidance and Counseling services